Building an OT Security Microgrid Testbed - Gyebnar, Gergó (Academic and Applied Research in Military and Public Management Science, 2024)
This paper introduces the development of an Operational Technology (OT) security microgrid testbed. The testbed is aligned with the IEC 62443 standard and structured to simulate and mitigate potential security risks within OT systems. It serves as a platform for evaluating cybersecurity strategies through test scenarios and cases, aimed at enhancing the resilience and responsiveness of OT environments to cyber threats. The work described here lays the foundational framework for subsequent research, focusing on cybersecurity measures, including MITRE ATT&CK-based methodologies and detection strategies using machine learning. This initial exploration emphasises the importance of creating a versatile, realistic testing environment to understand and address the unique security challenges faced by OT systems.